Designing qualitative research - Marshall, Catherine (Sage Publications, 2006)
Includes bibliographical references (p. 219-243) and index.; Introduction -- The what of the study : building the conceptual framework -- The how of the study : building the research design -- Data collection methods -- Managing, analyzing, and interpreting data -- Planning time and resources -- Articulating value and logic.